PERENCANAAN CHECK DAMSUNGAI LEBUGINI KABUPATENKUDUS, JAWA TENGAH - Fikri Amirullah; Raditya Nalendro; Sri Eko Wahyuni; Salamun Salamun (Jurnal Karya Teknik Sipil, 2014)
Lebugini River is the branch of Juanariverswhich is under the authority of the Central River Region Pemali - Juana, precisely located in the administrative area of the Kudus District. The location, which is on the upstream,causes degradation of the river channel, thus, to stabilize the river channel, the local Goverment should have a plan to build the conservation building. The dataused for the planning of check dam areprimary data (geotechnical data, the geometry of Lebugini river, and also the water level when flood came) and secondary data (topographic map and rainfall data). These data is used as a basic ofmain dam planning, sub dam, apron, complementary buildings, building stability control, and as the  reference to determine the budget plan. From the calculation, height of main dam is 4,00 m, width of main dam’s and sub dam’s crest are 17,00 m each, thick of main dam’s and sub dam’s crest are 1,50 m each, the upstream slope of the dam is around 1 : 0,5, the downstream slope of the dam is around 1 : 0,2, width of main dam’s and sub dam’s wing are 1,50 m each, both main dam’s and sub dam’s wing penetration are 2,00 m each, height of sub dam 1,60 m, length of apron is 11 m, square -shaped drip hole with sides 1,00 m by 11 pieces. The total cost to build the check dams of Lebugini River is IDR 1.521.177.000,00 include VAT and 110 days workmanship.